Mesenteric ischemia in pregnancy - a catastrophe: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Mesenteric ischemia is a rare condition with a high mortality rate of 24-94%. Acutely, it occurs because of sudden vascular emboli or thrombi and presents with severe abdominal pain disproportionate to physical examination findings with other nonspecific symptoms.Case presentation: A para 2+0 gravida 3 presented at 36 weeks 4 days of gestation with a 1-day history of worsening lower abdominal pain radiating to the back and reduced fetal movements. Mild pallor was observed, and vaginal examination showed a latent phase of labor. Shortly after admission, the patient developed diaphoresis and mild confusion with worsening pain, and an urgent ultrasound confirmed intrauterine fetal demise. Subsequently, she developed dizziness and progressed to loss of consciousness, with resuscitation promptly begun but unsuccessful. A diagnosis of extensive mesenteric ischemia was made postmortem.Discussion: Bowel ischemia can result from occlusions of major abdominal vessels and progress to necrosis, gangrene, and eventually perforation with subsequent severe complications. Uterine vasoconstriction in pregnancy itself contributes to a hypercoagulable state, increasing the risk of mesenteric ischemia, with a 10-fold higher risk in those conceiving by in vitro fertilization and embryo transfer. Other venoocclusive causes include atrial fibrillation, coagulopathic, malignancy, and radiation. Diagnosis is mainly by computed tomography. Confirmation is made by emergency laparotomy and histology. Blood investigations like lactate levels may be elevated in sepsis and screening for coagulopathies after diagnosis is made is indicated. Management involves anticoagulants, thrombolysis, and surgical interventions, such as resection and anastomosis, or endarterectomy, and anterograde bypasses. Masked symptoms, rapid progression, and severe resource limitations made this a difficult case to diagnose and manage.Conclusion: Given the rarity of the incidence of mesenteric ischemia, a very high level of suspicion is required to diagnose and promptly manage this emergency.